Role of cervids and wild boar on the presence of tick-borne encephalitis virus in Sweden - Gómez Martínez, Carmelo (2014)
Roe deer have been historically considered the main large mammal host for Ixodes ricinus ticks and it has been related with the current distribution and prevalence of tick-borne encephalitis virus in Sweden, being the main arguments the roe deer population peak and a series of mild winters in the nineties. Nowadays, roe deer is again at levels similar to the seventies, but the virus incidence and ticks abundance are still increasing. The role that other large mammal species play on this could be important to understand the current situation. We analysed the presence or absence of tick-borne encephalitis virus antibodies on 259 individuals of fallow deer, moose, red deer, roe deer and wild boar from blood samples collected by hunters during the hunting seasons of 2010 to 2013 in 31 municipalities. The results show infection in individuals of the five species, with the highest prevalence in roe deer, followed by moose, red deer, wild boar and fallow deer. However, the differences among the species are not significant. We also found that the age and sex of the individuals affect the probability of infection. This study demonstrates that not only roe deer, but the other four species analysed are important hosts for tick-borne encephalitis virus and they should be taken into account in the management of the wild populations to prevent an increase of the human infections.